2008
DOI: 10.1162/jocn.2008.20047
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Primate Orbitofrontal and Dorsolateral Prefrontal Neurons: Effect of Reward Schedule on Task-related Activity

Abstract: Recent studies show that task-related activity in the dorsolateral prefrontal cortex (DLPFC) is modulated by the quality and quantity of the reward, suggesting that the subject's motivational state affects cognitive operations in the DLPFC. The orbito-frontal cortex (OFC) is a possible source of motivational inputs to the DLPFC. However, it is not well known whether these two areas exhibit similar motivational effects on task-related activity. We compared motivational effects on task-related activity in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
3
24
0
1
Order By: Relevance
“…Indeed, recent empirical work has suggested that lateral PFC is preferentially involved in active maintenance of goal-related information (30)(31)(32)(33)(34)(35). Interestingly, PFC neurons also code information related to the reward context (3,7,36). Thus, a primary implication of our findings is that the right lPFC represents goal-relevant information (e.g., task rules; ref.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Indeed, recent empirical work has suggested that lateral PFC is preferentially involved in active maintenance of goal-related information (30)(31)(32)(33)(34)(35). Interestingly, PFC neurons also code information related to the reward context (3,7,36). Thus, a primary implication of our findings is that the right lPFC represents goal-relevant information (e.g., task rules; ref.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have explored neural mechanisms that underlie reward expectancy effects across a range of cognitive domains (4)(5)(6)(7)(8)(9)(10)(11). These studies have consistently demonstrated that increasing trial reward value is associated with increasing transient activity on such trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estudios recientes sugieren que esta regi贸n se relaciona con la integraci贸n de la informaci贸n cognitiva y motivacional (Ichihara-Takeda y Funahashi, 2008;Watanabe y Sakagami, 2007), ya que se considera fundamental en la representaci贸n y mantenimiento activo de la informaci贸n relativa a la meta bajo condiciones que favorecen el control proactivo (Grandjean y cols., 2012;Lesh y cols., 2013); en el mantenimiento de las reglas y normas para realizar de forma correcta la tarea y obtener una recompensa por ello (Jimura, Locke y Braver, 2010;Miller y Cohen, 2001); y en la creaci贸n de una representaci贸n mental de la informaci贸n relativa al contexto necesaria para ejecutar la tarea y actualizarla en funci贸n de sus consecuencias (Feil y cols., 2010).…”
Section: Regiones Cerebrales -C贸rtex Prefrontal Lateral (Lpfc: Del Inunclassified